2014
DOI: 10.1103/physrevc.90.034619
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of statistical model calculations for stable isotope neutron capture

Abstract: It is a well-observed result that different nuclear input models sensitively affect Hauser-Feshbach (HF) crosssection calculations. Less well-known, however, are the effects on calculations originating from nonmodel aspects, such as experimental data truncation and transmission function energy binning, as well as code-dependent aspects, such as the definition of level-density matching energy and the inclusion of shell correction terms in the level-density parameter. To investigate these aspects, Maxwellian-ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…Apart from this explicit level-structure dependence, whenever the excitation energies of the residue nucleus are greater than the last experimentally-known level, the sum of transmission coefficients over spins and parities must be replaced by an integral over the level density. Beard et al studied this "truncation" effect by varying the maximum number of known levels in their calculations and found that their Maxwellian-averaged neutron-capture cross sections changed by almost 20% [13].…”
Section: Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Apart from this explicit level-structure dependence, whenever the excitation energies of the residue nucleus are greater than the last experimentally-known level, the sum of transmission coefficients over spins and parities must be replaced by an integral over the level density. Beard et al studied this "truncation" effect by varying the maximum number of known levels in their calculations and found that their Maxwellian-averaged neutron-capture cross sections changed by almost 20% [13].…”
Section: Structurementioning
confidence: 99%
“…We chose this code because it has been extensively used in many sensitivity studies involving neutron-capture reactions (e.g. [13,17]). Unlike TALYS, NON-SMOKER does not include the pre-equilibrium or direct components.…”
Section: A Talys and Non-smokermentioning
confidence: 99%
See 1 more Smart Citation
“…The code NON-SMOKER, used to generate the thermonuclear reaction rate library REACLIB [34] also used the CT+BSFG level density description. However it is important to stress that the implementation of the CT+BSFG model in NON-SMOKER differs from that of TALYS in a number of key respects, including the definition of the back-shift, level density and spin-cut off parameters, as well as the temperature and the CT+BSFG matching point energy [35]. When generating the BRUSLIB library [18], TALYS was operated using microscopic model 5 in the above list.…”
Section: A Level Densitymentioning
confidence: 99%
“…RIPL-3 [6], which can be used in calculation of the statistical decay. Both the phenomenological nature of the description and the variation between models contribute to the uncertainty in the prediction of capture cross sections [7] which is further compounded by the choice of implementation in Hauser-Feshbach codes [8]. Among these models, one of the most widely used is the Generalized Lorentzian model of Kopecky et al [9].…”
Section: Introductionmentioning
confidence: 99%